Microfinance In Laos: A Case for Women's Banking? - Hans Dieter Seibel; Carmen R. Kunkel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
During the last ten years, the Government of The Lao PDR, a communist country, has taken bold steps towards a market economy, creating a policy environment for the emergence of a demand-driven system of microfinance. Such a system should be based on the cultural traditions of Laos where community solidarity is strong and women play a crucial role in microfinance. It is suggested that an evolving Laotian system of microfinance might comprise the following components: (1) A microfinance section in the central bank to provide an appropriate policy, legal and supervisory framework; (2) Commercial banks as microfinance wholesalers and retailers - to be reformed through five strategies: (a) an incentive strategy: converting branches or sub-branches into profit centers which mobilize their own resources and provide credit at their own risk; (b) a sound banking strategy: geared to institutional viability and sustainable financial services; (c) a linkage strategy: linking banks with non-formal financial institutions/financial SHGs; (d) an outreach strategy: extending the banking services to increasing numbers of women and men, including the poor; and (e) a transformation strategy: transforming branches or sub-branches branches or sub-branches into autonomous financial institutions owned and managed by local people; (3) A network of semiformal, and eventually formal, women's village banks for both women and men; and (4) Savings and credit associations functioning as informal self-help banks of microbusiness-women. Based on deeply entrenched cultural traditions, women have the potential of becoming the microfinance bankers of Laos, building viable institutions with sustainable financial services, for all segments of the population, including women and the poor.
Keywords: 330; Mikrofinanzierung; Frauen; Laos